Severely Impaired Bone Material Quality in Chihuahua Zebrafish Resembles Classical Dominant Human Osteogenesis Imperfecta. (15th June 2018) - Fiedler, Imke A.K.; Schmidt, Felix N.; Wölfel, Eva M.; Plumeyer, Christine; Milovanovic, Petar; Gioia, Roberta; Tonelli, Francesca; Bale, Hrishikesh A.; Jähn, Katharina; Besio, Roberta; Forlino, Antonella; Busse, Björn
ABSTRACT: Excessive skeletal deformations and brittle fractures in the vast majority of patients suffering from osteogenesis imperfecta (OI) are a result of substantially reduced bone quality. Because the mechanical competence of bone is dependent on the tissue characteristics at small length scales, it is of crucial importance to assess how OI manifests at the micro‐ and nanoscale of bone. In this context, the Chihuahua ( Chi/+ ) zebrafish, carrying a heterozygous glycine substitution in the α1 chain of collagen type I, has recently been proposed as a suitable animal model of classical dominant OI, showing skeletal deformities, altered mineralization patterns, and a smaller body size. This study assessed the bone quality properties of Chi/+ at multiple length scales using micro‐computed tomography (micro‐CT), histomorphometry, quantitative back‐scattered electron imaging, Fourier‐transform infrared spectroscopy, nanoindentation, and X‐ray microscopy. At the skeletal level, the Chi/+ displays smaller body size, deformities, and fracture calli in the ribs. Morphological changes at the whole bone level showed that the vertebrae in Chi/+ had a smaller size, smaller thickness, and distorted shape. At the tissue level, Chi/+ displayed a higher degree of mineralization, lower collagen maturity, lower mineral maturity, altered osteoblast morphology, and lower osteocyte lacunar density compared to wild‐type zebrafish. The alterations in the cellular, compositional, and structural properties of Chi/+ bones bear an explanation for the impaired local mechanical properties, which promote an increase in overall bone fragility in Chi/+ . The quantitative assessment of bone quality in Chi/+ thus further validates this mutant as an important model reflecting osseous characteristics associated with human classical dominant OI. © 2018 American Society for Bone and Mineral Research.